How does thiol/disulfide homeostasis change in prediabetic patients?. Issue 2 (November 2015) - Ates, Ihsan; Kaplan, Mustafa; Inan, Bayram; Alısık, Murat; Erel, Ozcan; Yilmaz, Nisbet; Guler, Serdar
Highlights: Examine thiol/disulfide homeostasis in prediabetic patients. Thiol–disulfide exchanges were examined using the newly developed automated method. We have shown for the first time that thiol oxidation increases in prediabetes. There is a positive correlation between the disulfide and FBG and HbA1c levels. Abstract: Aims: Our aim was to examine thiol/disulfide homeostasis, which has a critical role in many cellular activities such as antioxidant protection, detoxification, cell growth and apoptosis, in prediabetic patients. Methods: The study population was formed of a total of 250 participants; 125 (54 males, 71 females) of which were newly diagnosed with prediabetes, aged over 18 and who had not received any prior treatment and 125 (52 males, 73 females) healthy volunteers. Prediabetic patients were diagnosed using a glucose tolerance test. In both groups, native thiol–disulfide exchanges were examined using the automated measurement method newly developed by Erel and Neselioglu. Results: When compared to the control group, the native thiol ( p < 0.001) and total thiol ( p = 0.008) levels, and the native thiol/total thiol ( p = 0.022) ratio was lower; while disulfide ( p = 0.001) level and, disulfide/native thiol ( p = 0.003) and disulfide/total thiol ( p = 0.022) ratios were higher in prediabetic patients. A positive correlation was determined between disulfide and the fasting blood glucose levels ( r = 0.394, p = 0.017) and glycolysed hemoglobin (HbA1c) ( r = 0.307, p = 0.011). On the other hand, a negative correlation was determined between native thiol and fasting blood glucose levels ( r = −0.335, p = 0.004). Conclusion: With this study, we have shown for the first time that thiol oxidation increases in prediabetic patients and that there is a positive correlation between the disulfide and blood glucose and HbA1c levels.